Guidelines for the effective use and procurement of advanced warning arrow panels. - Mace, Douglas J.; Finkle, Mark; Pennak, Sara (Research results digest (National Cooperative Highway Research Program), 2001)
This digest summarizes the results of NCHRP Project 5-14, "Advanced warning arrow panel visibility" ... [and] is based on a draft final report prepared by Douglas Mace, Mark Finkle, and Sara Pennak ...